Aquablation therapy in large prostates (80–150 cc) for lower urinary tract symptoms due to benign prostatic hyperplasia: WATER II 3‐year trial results. Issue 2 (28th October 2021) - Zorn, Kevin C.; Bidair, Mohamed; Trainer, Andrew; Arther, Andrew; Kramolowsky, Eugene; Desai, Mihir; Doumanian, Leo; Elterman, Dean; Kaufman, Ronald P.; Lingeman, James; Krambeck, Amy; Eure, Gregg; et al.
Abstract: Objective: The objective of this study is to determine if Aquablation therapy can maintain its effectiveness in treating men with lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH) with large‐volume (80–150 cc) prostates at 3 years. Subjects and Methods: One hundred one men with moderate‐to‐severe BPH symptoms and prostate volumes between 80 and 150 cc were enrolled in a prospective, nonrandomized, multicenter, international clinical trial in late 2017. Baseline, procedural, and follow‐up parameters were recorded at baseline and scheduled postoperative visits. IPSS, Qmax, and treatment failure are reported at 3 years. Results: The mean prostate volume was 107 cc (range 80–150). Mean IPSS improved from 23.2 at baseline to 6.5 at 3 years (16.3‐point improvement, p < 0.0001). Mean IPSS quality of life improved from 4.6 at baseline to 1.1 at 3 years (improvement of 3.4 points, p < 0.0001). Maximum urinary flow increased from 8.7 to 18.5 cc/s. At 3 year follow‐up, 6% of treated patients needed BPH medication and an additional 3% required surgical retreatment for LUTS. Conclusions: Three‐year follow‐up demonstrates a sustained symptom reduction response along with low irreversible complications to Aquablation in men with LUTS due to BPH and prostates of 80–150 cc. Current treatment options available for men with prostates of this size have similar efficacy outcomes but are burdened with high rates of irreversible complications. There are now numerous clinical studies with Aquablation used in various prostates sizes, and it should be offered as an option to men with LUTS due to BPH.